Jake and Lily - Spinelli, Jerry (New York, N.Y. : Balzer + Bray, 2012)
"Jake and Lily are twins and have always felt the same--like two halves of one person--but the year they turn eleven and Jake begins hanging out with Bump Stubbins, everything changes"--Provided by publisher.
480
Keywords: Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Individuality -- Juvenile fiction; Bullies -- Juvenile fiction; Friendship -- Juvenile fiction